2021
DOI: 10.1111/vop.12861
|View full text |Cite
|
Sign up to set email alerts
|

Does the order of intraocular pressure measurement affect tonometry results?

Abstract: Purpose To determine whether the order of intraocular pressure (IOP) measurement affects readings, regardless of which eye is measured first. Methods Intraocular pressure was measured in 31 and 41 dogs using applanation and rebound tonometry, respectively. Initially, IOP was measured in the first (randomly chosen) eye (reading A), followed by measurement in the fellow eye (reading B), and a third (repeated) measurement in the first eye (reading C). After 15 minutes, measurements were repeated in reverse order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Goldmann applanation tonometry is likely subject to an intereye order effect, with intraocular pressure measured higher in the first eye measured than in the second eye measured, both in healthy subjects 18 and in subjects with ocular hypertension 19 . Similar results have been reported for pneumotonometry 20 and for rebound tonometry 21 . It is unknown whether the tonometry values and the ocular biomechanical parameters of the ORA or of the CorVis ST also differ between the two eyes.…”
mentioning
confidence: 60%
“…Goldmann applanation tonometry is likely subject to an intereye order effect, with intraocular pressure measured higher in the first eye measured than in the second eye measured, both in healthy subjects 18 and in subjects with ocular hypertension 19 . Similar results have been reported for pneumotonometry 20 and for rebound tonometry 21 . It is unknown whether the tonometry values and the ocular biomechanical parameters of the ORA or of the CorVis ST also differ between the two eyes.…”
mentioning
confidence: 60%
“…Additionally, this study only monitored heart rate to investigate potential systemic side effects, while future studies could consider assessing blood pressure as well given the reported vasodilating effects of NO donors. The effect of multiple IOP readings within one visit is an additional limit to this study, as repeated tonometry within one visit could result in significant reductions in IOP, though this may not be clinically appreciable (Pe'er et al., 2021 ). This limitation is unavoidable in studies where repeated IOP measurements are required; however, ensuring that study participants receive the same number of measurements at the same frequency can reduce variability.…”
Section: Discussionmentioning
confidence: 99%